Tinjauan Fiqih Muamalah Tentang Jual Beli Gas LPG Bersubsidi Tiga Kg Melebihi Harga Eceran Tertinggi (HET) (Studi di Pangkalan Gas Ciateul Garut) - Gaussian, Gini; Alghifari, M. Dzikri (Jurnal Hukum Ekonomi Syariah, 2024)
This study discusses the practice of selling 3 kg subsidized LPG gas at Bu Rita Nengsih's gas depot, which does not comply with government regulations or Islamic law, as the selling price exceeds the highest retail price (HET). The reason for this is the additional fee of Rp1,000 per cylinder requested by the gas couriers. The community continues to purchase the gas because it is a basic necessity. The research problems addressed in this study include the determination of prices above HET in the sale of subsidized LPG gas at the gas depot and a fiqih muamalah review of this price determination. This research uses a field research method with a qualitative approach, which is descriptive and analytical in nature. The results of the study show that the sale of 3 kg subsidized LPG gas above HET contradicts government regulations and does not comply with Islamic law.  Keywords: Muamalah Fiqh, Buying and Selling, Highest Retail Price